2014
DOI: 10.1136/bcr-2014-206931
|View full text |Cite
|
Sign up to set email alerts
|

Rectal ulcer associated with SpaceOAR hydrogel insertion during prostate brachytherapy

Abstract: We present a case of rectal ulceration associated with SpaceOAR hydrogel insertion during low-dose-rate (LDR) brachytherapy in a patient with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 16 publications
(4 reference statements)
2
43
1
Order By: Relevance
“…Our present work builds upon published studies examining the use of HS in our region . In particular, our present findings are comparable to three studies that have reported on rectal dose endpoints and toxicities (late Grade 1), and found them to be significantly lower across all patient groups, with the greatest difference observed in the higher rectal dose (rV 65–82 ) range.…”
Section: Discussionsupporting
confidence: 87%
“…Our present work builds upon published studies examining the use of HS in our region . In particular, our present findings are comparable to three studies that have reported on rectal dose endpoints and toxicities (late Grade 1), and found them to be significantly lower across all patient groups, with the greatest difference observed in the higher rectal dose (rV 65–82 ) range.…”
Section: Discussionsupporting
confidence: 87%
“…Radiation-induced intestinal side effects such as bleeding and ulcer were sometimes observed [22][23][24], but rectal perforation associated with RT is rarely observed. On the contrary, a case of rectal ulceration due to insertion of SpaceOAR into the anterior rectal wall was reported by Teh AY et al [25]. However, in this case, we con rmed by MRI, that SpaceOAR was inserted into the correct space between the prostate and rectum.…”
Section: Discussioncontrasting
confidence: 50%
“…It should be noted that whilst a number of clinical studies have reported hydrogel spacers to be safe [3,6], one published case report linked a rectal ulcer to a hydrogel insertion [28] and their use was halted in a recent trial, where two rectal fistulas were presumed due to the gradual accumulation of gel within the confines of the anterior rectal wall, as seen on magnetic resonance imaging during the course of the treatment [29]. However, the latter publication reported that in addition to gel migration, variations in individual patient radiosensitivity could have played a role, on-treatment image guidance was limited to orthogonal x-rays (it did not state whether alignment based on bony anatomy or prostate fiducials), and the in vivo dose to the anterior rectal wall was not known precisely [29].…”
Section: Discussionmentioning
confidence: 99%